Application of a software code metrics at the early stage of the software life cycle - Евсеев, Владислав Вячеславович (Eastern-European Journal of Enterprise Technologies, 2012)
The analysis of basic programmatic сode birth-certificates application is conducted on the early stage of technological preproduction corporate informative systems software planning